PENGARUH PENGGUNAAN MEDIA POP-UP BOOK TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV UPT SPF SDN MANNURUKI - Mulya Ramadani, Suci; Nasrah; Nasharuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes in Natural and Social Science (IPAS) among elementary school students and the suboptimal use of innovative learning media in the learning process. Therefore, it is necessary to have learning media that can increase student engagement and understanding. This study aims to determine the effect of Pop-Up Book media on the IPAS learning outcomes of fourth-grade students at UPT SPF SDN Mannruki. This research uses a Quasi-Experimental method with a Nonequivalent control group design. The population in this study consists of fourth-grade students at UPT SPF SDN Mannuruki, totaling 54 students. The data collection technique used is total sampling. The instrument used is a test instrument in the form of multiple-choice questions to measure student learning outcomes with a Pretest-Posttest Control group design. Research results show that the learning outcomes of science students in the experimental class using Pop-Up Book media obtained an average score of 80.77, while in the control class that did not use Pop-Up Book media, the average score was 66.61. The t-test results obtained (0.001 < 0.05). Thus, it can be concluded that the use of Pop-Up Book media has a significant effect on student learning outcomes.